THE EFFECT OF FIRST AID SKILLS TRAINING ON RING-JUSTED FINGER MANEUVERS - Aji, Rustam; Dewi Lusiani; Sherly Ratih Frichesarius Santy Aji; Roro Ajjie Ayuningtyas; Tonny Cortis Maigoda; Indah Fitri Andini; Sulistiyani, Sulistiyani (Bajang Institute, 2024)
Finger injuries due to being caught in a ring, if stuck for too long can inhibit blood circulation to the finger, thereby risking causing serious permanent damage. The research subjects are class VI students at SDN 7 Rejang Lebong, with long experience as UKS members according to predetermined criteria. This research used primary data from 36 students, who were willing and agreed to become respondents. Observational research, cross sectional study design. The data results were analyzed using the chi-square test. The results of Chi-square analysis obtained a value of P = 0.04 < α 0.05. So Ho is rejected and Ha is accepted, meaning that statistically there is a significant relationship between first aid skills and the maneuver of a finger caught in a ring. So that students who have been trained can be active members of the UKS and PMR teams, to be helpers if there is a case of a finger being caught in a ring. It is recommended to plan regular training activities specifically for other classes.